The temperature dependence of single-event transients in 90-nm CMOS dual-well and triple-well NMOSFETs - 李达维 秦军瑞 陈书明 (Chinese physics B, 2013)
This paper investigates the temperature dependence of single-event transients（SETs） in 90-nm complementary metat-oxide semiconductor（CMOS） dual-well and triple-well negative metal-oxide semiconductor field-effect transistors（NMOSFETs）.Technology computer-aided design（TCAD） three-dimensional（3D） simulations show that the drain current pulse duration increases from 85 ps to 245 ps for triple-well but only increases from 65 ps to 98 ps for dual-well when the temperature increases from-55℃ to 125℃,which is closely correlated with the NMOSFET sources.This reveals that the pulse width increases with temperature in dual-well due to the weakening of the anti-amplification bipolar effect while increases with temperature in triple-well due to the enhancement of the bipolar amplification.